Atypical cartilaginous tumor imaging findings in the distal phalanx of the left thumb: case report and literature review - Wang, Hong; Tang, Xinyi; Wang, Yuting; Peng, Xiaoyan; Yang, Yujia (Frontiers in Oncology, 2025)
BackgroundAtypical cartilaginous tumors (ACTs) usually occur in long bones rather than in the hands or feet. To date, detailed imaging features of ACTs in the hands or feet were reported in only a few case reports.Case presentationWe report a case of an Asian woman in her early 80s who presented to our hospital with a painless mass in the distal phalanx of the left thumb. Radiography and computed tomography (CT) showed osteolytic destruction and cortex thickening in the distal phalanx with extension into soft tissue. Magnetic resonance imaging (MRI) demonstrated a local soft tissue signal mass with isosignal intensity in T1 and heterogeneous high-signal intensity in T2. Color Doppler ultrasound suggested that the tumor was hypovascularized. The patient underwent amputation, and histological analysis revealed an ACT. The patient’s symptoms improved postoperatively, with no recurrence as of the 3-year follow-up.ConclusionMeanwhile, this study also reviewed the comparable diagnostic methods of ACT and chondrosarcoma. The analysis of previous similar cases showed that preoperative imaging diagnosis of ACT can be challenging and multimodal imaging appears to be beneficial in diagnosing ACTs and malignant chondrosarcoma grade II/III in the hands and feet.